Readily biodegradable and low-toxic biocompatible ionic liquids for cellulose processing. Issue 90 (13th September 2016) - Markiewicz, Marta; Maszkowska, Joanna; Nardello-Rataj, Véronique; Stolte, Stefan
Abstract : Ecotoxicity and biodegradability of ILs intended for cellulose processing were tested. Betaine-ester levulinate exhibits low environmental hazard potential (full degradability, low toxicity). Other ILs were partially degradable and moderately toxic. Abstract : Cellulose is an important feedstock for the chemical industry, but its processing is a challenge. Considerable efforts have been invested in applying the rules of green chemistry in developing environmentally more acceptable processes. Within this work we present an account on biocompatible, degradable ILs of low (eco)toxicity which could find potential applications in the cellulose processing industry. We have tested ILs based on choline and betaine cations and the levulinate anion. We have discovered that, among these structures, betaine-ester levulinate is the most degradable and the least toxic IL. All tested structures were to some, sometimes high, extent degradable and showed low to moderate toxicity towards Daphnia magna, Vibrio fischeri and rat leukaemia cells.